2018
DOI: 10.1111/resp.13399
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure non‐invasive ventilation during exercise in COPD patients with chronic hypercapnic respiratory failure: A randomized, controlled, cross‐over trial

Abstract: Background and objective Patients with chronic obstructive pulmonary disease (COPD) and chronic hypercapnic respiratory failure (CHRF) characteristically have exercise intolerance and limitations in performing conventional training. Therefore, the aim of this study was to investigate the acute effects of non‐invasive ventilation (NIV) as a supportive tool during exercise in CHRF. Methods Two cycle endurance tests (CET) at 60% of the peak work rate were performed. Patients were randomly assigned to cycle in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 39 publications
2
39
1
Order By: Relevance
“…The study by Gloeckl et al . provides new hope for these patients . Using a randomized cross‐over trial design, these investigators found that the use of NIMV in these COPD patients with stable hypercapnic respiratory failure led to a 39% increase in endurance time on a cycle ergometer than oxygen therapy alone with lower arterial PaCO 2 and better oxygenation.…”
Section: Novel Approaches To Hypercapnic Respiratory Failurementioning
confidence: 99%
“…The study by Gloeckl et al . provides new hope for these patients . Using a randomized cross‐over trial design, these investigators found that the use of NIMV in these COPD patients with stable hypercapnic respiratory failure led to a 39% increase in endurance time on a cycle ergometer than oxygen therapy alone with lower arterial PaCO 2 and better oxygenation.…”
Section: Novel Approaches To Hypercapnic Respiratory Failurementioning
confidence: 99%
“…Furthermore, we need to study the effects of interventions combining traditional PR and palliative care with innovative medical treatments for patients with different but advanced chronic respiratory diseases. Such interventions may include the addition of high-flow oxygen therapy for patients with severe exercise-induced desaturation,97 non-invasive ventilation for patients with pronounced hyperinflation and/or hypercapnia,98 endobronchial interventions for patients with severe emphysema99 100 and biologicals for patients with severe obstructive lung diseases 101. Finally, we should aim for (combined) therapies that are supportive for the patient to take the responsibility as specialists of their own lives: patients must become co-creators of value care 102…”
Section: Future Directionsmentioning
confidence: 99%
“…In a recent publication in Respirology , Gloeckl et al . reported on the acute effects of NIV during cycling exercise in 20 patients with severe COPD and daytime hypercapnia.…”
mentioning
confidence: 99%
“…This finding is in keeping with a previous study using a high‐pressure ventilation strategy during ground walking in a similar group of COPD patients established on home bi‐level therapy showing improvements in oxygenation, dyspnoea and walking distance compared to oxygen therapy alone . It is important to note that, in the study by Gloeckl et al ., a highly select group of patients were enrolled, all of whom were very well acclimated to high inspiratory pressures, having used home NIV for a mean duration of 18 months. In addition, haemodynamic compromise with high‐pressure NIV is possible due to reduced venous return from high intra‐thoracic pressures .…”
mentioning
confidence: 99%
See 1 more Smart Citation